General Synod of the Church of Ireland: May 2018. (12th February 2019) - Turner, Kate
Abstract : This year's General Synod, the first meeting of the triennium, was held in the now familiar venue of a hotel in Armagh City. The Synod considered Bills relating to the Book of Common Prayer, safeguarding trust issues, the governance of St Fin Barre's Cathedral, temporary suspension of episcopal electoral colleges and General Synod membership. During the meeting of Synod a commentary on the Constitution of the Church of Ireland was launched.